HIV policy legacies, pandemic preparedness and policy effort to address COVID-19. - Ashley Fox; Heeun Kim (Public Library of Science (PLoS), 2023)
That the world was unprepared for a major infectious disease outbreak is now readily apparent to all credible observers. However, some countries were more prepared than others and we have seen a variety of responses to COVID-19 emerge across nations. While recognizing that the sources of variation in country responses to COVID-19 are many and varied, in this study we seek to examine how policy legacies from national responses to HIV have influenced countries' responses to COVID-19. The aim of this study was to examine whether countries with a more conducive HIV policy environment were better prepared for COVID-19 and have therefore had more preemptive and rights-based responses. Using data from the Oxford Covid-19 Government Response Tracker, we develop measures of country effort to respond to COVID-19 including early containment and closure policies, prevention policies, economic policies, and health system policies. We combine this with data from the HIV Policy Lab and correlate overall and disaggregated country HIV Policy scores with COVID-19 Policy scores. We find that the COVID-19 Containment and Closure Measures Index was negatively correlated with supportive social policies related to HIV in the early stages of the pandemic, but the association did not persist as time went on. The COVID-19 Economic Support Measures had prolonged positive associations with supportive social policies related to HIV and negative association with clinical and treatment policies. Countries with stronger structural responses to HIV have been less inclined towards involuntary measures and more prepared for the social and economic elements of COVID-19 pandemic response.